(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2020)
The study delineates the aquifer system of the study area and determines the extension of potential fresh water aquifer and suitable locations for groundwater development through geophysical electrical resistivity method. Vertical electrical sounding with Schlumberger electrode configuration, a method for surface resistivity measurement, has been used for data collection. Resistivity data along with borelog data analyses are used for this investigation. Lithological cross section analyses show that sand and clay dominated lithology with frequent facies changes occur throughout the area and also show an aquifer system similar to the three-tier aquifer system proposed by Aggarwal for coastal area of Bangladesh. This study reveals the presence of three aquifers. 1staquifer occurs at a very shallow depth at some places <5 m and thickness of the aquifer varies 10-70 m all over the region, and shows very low resistivity value indicating saline pore water. Average depth to the 2nd aquifer ranges from 60-70 m and also contaminated by saline water. In few places of 2nd aquifer resistivity values more than 20 Ωm suggest some fresh water pockets. Depth to the 3rd aquifer that spreads all over the study area is more than 220 m at maximum part of the area. Only potential fresh water aquifer is the 3rd or deep aquifer, but low resistivity values of this aquifer at Patharghata and small portion of Kalapara and Rangabali Upazilas hint that there may have saline water intrusion. More precise information for this complex geological set up require greater number of sounding points. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 8(1), 2019, P 11-18